IL-10 and IL-22 in Mucosal Immunity: Driving Protection and Pathology - Wei, Hua-Xing; Wang, Baolong; Li, Bofeng (Frontiers in Immunology, 2020)
The barrier surfaces of the gastrointestinal tract are in constant contact with various microorganisms. Cytokines orchestrate the mucosal adaptive and innate immune cells in the defense against pathogens. IL-10 and IL-22 are the most well studied members of the IL-10 family and play essential roles in maintaining mucosal homeostasis. IL-10 serves as an important regulator in preventing pro-inflammatory responses while IL-22 plays a protective role in tissue damage and contributes to pathology in certain settings. In this review, we focus on these two cytokines in the development of gastrointestinal diseases, including inflammatory bowel diseases (IBD) and colitis-associated cancer (CAC). We summarize the recent studies and try to gain a better understanding on how they regulate immune responses to maintain equilibrium under inflammatory conditions.